Alih Kode dan Campur Kode Bahasa Makassar dan Bahasa Indonesia pada Siswa Sekolah Menengah Pertama - Karmila Karmila; Asia M; Mahmudah Mahmudah (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. This study aims to describe (1) the manifestations of the use of code-switching in Makassar and Indonesian among students of SMPN 1 Takalar, (2) the manifestations of the use of code-switching in Makassar and Indonesian among students of SMPN 1 Takalar, and (3) the causes of code-switching. and mixed Makassar and Indonesian language codes for SMPN 1 Takalar students. This type of research is qualitative research with a qualitative descriptive research design. The data in this study were oral data in the form of words, clauses, phrases and sentences containing code-switching and code-mixing of Makassar and Indonesian languages originating from informants, namely students in grades 8.2, 8.3 and 8.4 at SMPN 1 Takalar which were taken during the conversation process between students when learning the local language takes place. Data collection was carried out using (1) the SBLC technique (free involvement technique), (2) the recording technique, and (3) the documentation technique.The results of this study indicate that there are three forms of code switching in class VIII students at SMPN 1 Takalar, namely (1) occurring between sentences, (2) occurring within sentences and (3) symbolic code switching that occurs on tags. There are two forms of code mixing, namely (1) insertion of elements in the form of words and (2) insertion of elements in the form of phrases, there are also two types of clauses (1) simplex clauses, and (2) complex clauses. Factors causing code switching and code mixing are (1) speakers/speakers, (2) listeners/oppositors, (3) the presence of a third party, (4) habits, (5) background of the speaker's attitude, (6) linguistic background or the language skills of SMPN 1 Takalar students.Keywords: Code Switching, Code Mixing, Makassar Language, Indonesian.